Development of interactive solar system diorama media to improve fifth-grade students’ critical thinking skills in elementary islamic school - Heri Irawan; Aan Widiyono (Lentera Negeri, 2026)
This study focuses on the lack of critical thinking skills and the low interest of students in class VA at Elementary Islamic School Darun Najah Srobyong, where the learning methods used still rely on static images. The purpose of this study is to design solar system diorama learning media that meet the standards of validity, practicality, and effectiveness in improving students' critical thinking abilities in Elementary Islamic School. The methodology applied in this study is Research and Development (R&D), which follows the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, observations, and pretest and posttest measurement instruments. The results show that this medium has a high level of validity, with scores reaching 87% from media experts and 90% from material experts. Statistical analysis conducted using a paired-sample T-test showed a significance value of 0,000, indicating a significant difference in students' critical thinking abilities before and after using the media. In addition, The N-Gain score analysis shows an average value of 0.3326 (33.26%), which categorizes the effectiveness of the media in the "moderate" group approaching low but relevant for use in learning. Therefore, it is concluded that the interactive solar system diorama is an appropriate and efficient tool for improving critical thinking abilities in Natural and Social Sciences (IPAS) learning at the elementary school level.